Dari Mimbar ke Layar: Livestreaming sebagai Model Pelayanan Digital dalam Transformasi Ibadah - Phileo Imanuel; Eka Putri Lago; Reni Triposa (Jurnal Salvation, 2026)
Abstract: The rapid development of digital technology has brought significant changes to church ministry practices, particularly in the conduct of worship services and congregational formation. In this context, livestreaming technology has evolved beyond a temporary or emergency solution and has become an integral part of contemporary church life. The continued use of livestreaming in church worship reflects a paradigm shift in ministry, moving from exclusively physical spaces toward digital spaces. This study aims to analyse livestreaming as a model of digital ministry in transforming worship practices. The research employs a qualitative approach through a literature review. The findings indicate that livestreaming contributes to a redefinition of the meaning of worship and congregational presence within virtual spaces. Furthermore, this practice opens new opportunities for interaction and the formation of broader faith communities, while simultaneously presenting challenges related to relational depth and the quality of spirituality. The novelty of this study lies in its conclusion that post-pandemic churches need to develop reflective and integrative digital ministries, ensuring that technology functions as a means to strengthen the church’s mission and inclusivity without displacing the essence of the Christian faith. Abstrak: Perkembangan teknologi digital telah membawa perubahan signifikan dalam praktik pelayanan gereja, khususnya dalam penyelenggaraan ibadah dan pembinaan jemaat. teknologi dalam pelayanan praktik livestreaming tidak berhenti sebagai solusi darurat, melainkan bertransformasi menjadi bagian integral dari kehidupan bergereja. Fenomena berlanjutnya penggunaan livestreaming dalam ibadah gereja menunjukkan adanya pergeseran paradigma pelayanan dari ruang fisik menuju ruang digital. Penelitian ini bertujuan untuk menganalisis livestreaming sebagai model pelayanan digital dalam mentransformasi praktik ibadah. Metode penelitian yang digunakan adalah pendekatan kualitatif melalui studi pustaka. Hasil kajian menunjukkan bahwa livestreaming berkontribusi pada redefinisi makna ibadah dan kehadiran jemaat dalam ruang virtual. Selain itu, praktik ini membuka peluang baru bagi interaksi dan pembentukan komunitas iman yang lebih luas sekaligus menghadirkan tantangan terkait kedalaman relasi dan kualitas spiritualitas. kebaharuan penelitian ini menyimpulkan bahwa gereja pasca-pandemi perlu mengembangkan pelayanan digital yang reflektif dan integratif agar teknologi berfungsi sebagai sarana yang memperkuat misi dan inklusivitas gereja tanpa menggeser esensi iman Kristen.